Comparative effects of La2O3 and Sm2O3 on structural and radiation shielding properties of WO3 enriched borate glassy-ceramics - Tasgin, Yahya; Yilmaz, Demet; Kanca, M. Sait; Yayla, Nihal; Kok, Mediha; Guler, Omer (Elsevier, 2026)
This research comprehensively investigates the impact of incorporating rare earth oxides -samarium oxide (Sm2O3) and lanthanum oxide (La2O3)-into a borate glassy-ceramic system enriched with tungsten oxide (WO3), with a focus on both structural characteristics and radiation shielding performance. SEM-EDS, elemental mapping, and XRD analyses conducted on the synthesized glassy-ceramic samples revealed that the incorporated rare earth oxides, Sm2O3 and La2O3, were uniformly distributed throughout the glassy-ceramic matrix. The results also confirmed that the glassy-ceramic retained its inherently amorphous structure. Moreover, the nominal doping levels of the rare earth elements were found to be in agreement with both the qualitative and quantitative results obtained from EDS measurements. Also, the gamma ray shielding parameters of synthesized glassy-ceramic samples were measured in absorption geometry with Am-241, Ba-133 and Ra-226 radioactive sources. The neutron shielding parameters were theoretically calculated. The 241Am-Be fast neutron source was used to measure the equivalent dose of neutron absorption. At an incident photon energy of 74.8 key, the mass attenuation coefficient of the tungsten oxide-enriched borate glassy-ceramic exhibited a remarkable improvement-rising by 17.98 % with the addition of 3 wt% Sm2O3 and by 11.58 % with the addition of 3 wt% La2O3. Notably, the N4 sample demonstrated a significant reduction in neutron-equivalent dose rate, reaching 19.80 % (mu Sv/h). The lead equivalent thicknesses (Pbeq) calculated at 356 key were 0.02397 cmPb for N0, 0.0391 cmPb for N1, 0.0403 cmPb for N4, and 0.0389 cmPb for N7. When benchmarked against the undoped N0 sample, the N4 and N7 compositions exhibited reductions in Pbeq values by approximately 68 % and 62 %, respectively, indicating a marked improvement in gamma shielding efficiency. Among all tested formulations, the Sm2O3-doped variant demonstrated superior gamma-ray attenuation capability relative to the La2O3-doped glassy-ceramic. Furthermore, the N4 sample achieved an impressive thermal neutron attenuation rate of 96.46 %, underscoring its strong potential as an effective dual-purpose shielding material against both thermal neutrons and ionizing gamma radiation.
Keywords: Radiation shielding; Fast and thermal neutron; Rare earth oxide; Borate glassy-ceramic